Peri‐lead edema after deep brain stimulation surgery for Parkinson's disease: a prospective magnetic resonance imaging study. (18th November 2018) - Borellini, L.; Ardolino, G.; Carrabba, G.; Locatelli, M.; Rampini, P.; Sbaraini, S.; Scola, E.; Avignone, S.; Triulzi, F.; Barbieri, S.; Cogiamanian, F.
Abstract : Background and purpose: The aim of this study was to define the prevalence and characteristics of peri‐electrode edema in a prospective cohort of patients undergoing deep brain stimulation (DBS) surgery and to correlate it with clinical findings. Methods: We performed brain magnetic resonance imaging (MRI) between 7 and 20 days after surgery in 19 consecutive patients undergoing DBS surgery for Parkinson's disease. The T2‐weighted hyperintensity surrounding DBS leads was characterized and quantified. Any evidence of bleeding around the leads was also evaluated. Clinical and follow‐up data were recorded. In a subgroup of patients, a follow‐up MRI was performed 3–6 weeks after surgery. We also retrospectively reviewed the post‐operative computed tomography scans of patients who underwent DBS at our center since 2013. Results: Magnetic resonance imaging showed a peri‐lead edematous reaction in all (100%) patients, which was unilateral in three patients (15.8%). In six patients (31.6%), we detected minor peri‐lead hemorrhage. Edema completely resolved in eight out of 11 patients with a follow‐up MRI and was markedly reduced in the others. Most patients were asymptomatic but six (31.6%) manifested various degrees of confusional state without motor symptoms. We found no significant correlation between edema volume, distribution and any clinical feature, including new post‐operative neurological symptoms. The retrospective computed tomography analysis showed that peri‐electrode hypodensity consistent with edema is absent at early post‐operative imaging but is common at scans performed >3 days after surgery. Conclusions: Peri‐electrode edema is a common, transient reaction to DBS lead placement and a convincing relation between edema and post‐operative clinical status is lacking.